Alternative Livelihood” Strategy to Improve Social Resilience of Fisher Households: a Case Study in Nembrala Village of Rote Ndao Regency - Chaterina Agusta Paulus; Yohanis Umbu L. Sobang (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
This  research is aimed to know the income of fishermen households, to analyze the contribution of alternative businesses to total income, to analyze the involvement of family members of the fishermen and the time spent to conduct alternative business of traditional fishermen in Nembrala Village, Rote Ndao Regency. Method of research is survey method through interview and observation technique. Respondents in this research as many as 35 people taken by purposive (intentionally). The data obtained were analyzed using descriptive analysis approach. The results showed that the average income of fishermen households for 1 year was Rp. 9,274,271.43 ± 853,574,82, the involvement of fishermen family members found that in the alternative activity of poultry and pigs dominantly done by the combination of female laborers (fisherman's wife) and child labor that is 51.43% and 42.86% respectively, while in the weaving bundle business is dominant done by female worker (wife of fisherman) equal to 48,57%, outpour time family member of fisherman at 3 (three) alternative effort is woman labor equal to 3,51 hour / day, child labor 2,57 hours / day , and man labor 1.13 hours / day. The result of this research can be concluded that alternative business need to be developed as a form of adaptation strategy of fisherman household in retaining earnings caused by decreasing income from main livelihood as fisherman due to seasonal change. The recommendation of this research is the development of alternative business by fisherman household in Nembrala Rote Ndao Regency can be improved and need to be supported by government policy through business capital facility and technology, so that alternative business role in increasing fisherman household income is more optimal.Key words: Resiliensi, alternative livelihood, Rote Ndao